Records management practices of selected student organizations in the University of the Philippines Diliman - Zulueta, Nicole R.; Golfo-Barcelona, Mary Grace, P. (Quezon City School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Student organizations are a part of a students' life in the university. The University of the Philippines Diliman houses several student organizations that conduct multiple activities and projects throughout the year. They produce records that are essential for the organization to function in the following years. Unfortunately, the university archives have yet to include them in their collection. Given that, they are expected to be the ones handling their own records for their own purposes specially since records management is essential in the operations of an organization. The study surveyed and interviewed five selected student organizations in order to identify and evaluate their records management practices.

The findings showed that most student organizations are unaware of the standards for records management and have no established records management policies. Despite that, they have recordkeeping practices that they have acquired through experience which they evaluate for further improvement. Most of student organizations have a records committee, with the secretary or secretariat as the committee head, who is mainly in charge of the organizations' records. The Survey results reflect that all of the organizations' compliance rating the ISO 15489 is below 31% which ultimately reflects the lack of records management policies.
Thesis (Bachelor of Library and Information Science)